LAW AND CIVILIZATION: NORBERT LIAS AS A REGULATION THEORIST - Jusmadi, Jusmadi; Haironi, Haironi; Masyduki, Masyduki; Jusnaidi, Jusnaidi; Helman, Mhd; Misran, Misran; Cuadmadja, Anera Irinsyahinta; Fikri, KMS. Novyar Satriawan (International Journal of Multidisciplinary Research and Literature, 2025)
German sociologist Norbert Elias devised a comprehensive sociological analysis of the interconnections between the processes of state formation, institutional dynamics, individual subjectivity, habitus, and the logic of their transformation over time. The historical sociology of the self, violence, crime and punishment, organizations, emotions, sexuality, social control, and sports are just a few of the many areas in which his work has significantly influenced social scientific thinking. His views have only sometimes been applied to other areas of law and social science study, with his influence in legal academia centered on criminology. This review emphasizes the potential future directions in which Elias's process-figurational approach could advance in sociolegal research and scholarship by outlining (a) the core elements of Elias's "process-figurational" sociology and his analysis of processes of civilization and decivilization, (b) Elias's observations on law and state formation; (c) a selection of the sociolegal research related to his sociological approach, in fields such as crime and punishment, evolving modes of regulation, and international relations; and (d) the potential future directions in which Elias's process-configurational approach might move in sociolegal research and scholarship. These encompass the emotive aspects of family law, human rights, and humanitarianism, as well as the interfaces between legal evolution and broader social change, legal pluralism and legal culture, tort law, constitutionalism, and the rule of law